The Origins of Chinese Influence on Pottery in the Tang and Song Dynasties (Al-Academy, 2017)
This research study of influence of Chinese thought on porcelain in the tang and song period, the study came into four sections, which are:* First section contains general framework of the research, which include the problem, which is represented by following of questions:1- Is there intellectual and ideological dimensions in Chinese porcelain?2-What are the mechanisms and techniques of Chinese porcelain?.the importance of this research and the need counted as a study providing cognitive addition into the Chinese arts field, especially ceramics of the Chinese. The aim of the research included of areas of artistic creativity in Chinese pottery and ceramics according to the bases of construction and composition. As the importance of research, lies in the promise of the study provide added knowledge in the field of Chinese porcelain. The objectives of this study were the disclosure of intellectual and ideological dimensions and its impact on Chinese porcelain. The study deals with the period between (9 to 12) and a place of (China) .The researcher defined the terminology whom it were mentioned inside this search*Second section has included theoretical framework of the research so it contains three divisions, which are: The first topic dealt with Chinese thought. The second historical references china. The third topic of Chinese motifs and methods of formation*Third section has included procedures of the research and has chosen three samples and then analyzed them within the descriptive and analytical way.*Fourth section has been specialized in order to show the results and conclusions as well as recommendations, proposals and index of research sources